Complementos oracionais na Redação ENEM: uma análise semântico-pragmática - Gabriella Pedrosa Santos Cunha (2021)
Transitive verbs with their full meaning have an internal argument, which can often be expressed by a subordinate clause - that functions as a direct or indirect object. We search, in this dissertation, to analyze this structure in essays that fit into the textual type of argumentative texts demanded by ENEM (Exame Nacional do Ensino Médio). The proposal of the research is a data analysis beyond the syntactic constituent and mediated by the correlation between its semantic and pragmatic components, considering the intentions and the attitudes of the speaker, regarding their speech. This research is based on textual theories, and the expositions of Baktin (2011), Adam (2008) and Perelman e Olbrechts-Tyteca (2005) uphold the analysis of the structure and features of ENEM’s essay. Thereafter, grounded by the functionalist grammar and the studies of Palmer (2011), Hengeveld (1988), Willet (1988) and Lyons (1977) on modal operators, we seek to present that verbs with complement clauses work as modality markers in the essays, which means, they operate on the event described by the subordinate clause, changing the speaker’s attitude towards this event. The study concluded that there are three types of modality related to complement clauses in ENEM’s essay. The first one is the epistemic modality, that points out the preposition’s factual state; it frequently occurs at the beginning and the end of an argumentative paragraph. The second one is the evidentiality, in which the preposition’s factual state is supported - more frequent in the argumentation development. At last, the third one is the deontic modality, occurring usually in paragraph’s or the text’s conclusion; it presents orders or suggestions. Finally, we aim to relate both theories and to point out the importance of complement clauses and their modalities in the writing process of ENEM’s essay.